Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil - Benetti, Cesar João; Hamada, Neusa (Zootaxa, 2016)
The monotypic Neotropical genus Claudiella Reichardt & Vanin, 1976 is currently known only from Brazil (C. ingens Reichardt & Vanin, 1976). We describe here three new species from Brazil, C. jefersoni sp. n., C. jeaneae sp. n. and C. anamariae sp. n., from Roraima, Minas Gerais and Bahia states, respectively, bringing to four the number of species included in Claudiella. These species can be distinguished by different characteristics observed in the legs, mouth parts, metathoracic wings and male genitalia.